2019
DOI: 10.1103/physrevapplied.12.014017
|View full text |Cite
|
Sign up to set email alerts
|

Benefit from Photon Recycling at the Maximum-Power Point of State-of-the-Art Perovskite Solar Cells

Abstract: Photon recycling is required for a solar cell to achieve an open-circuit voltage and power conversion efficiency (PCE) approaching the Shockley-Queisser theoretical limit. The achievable performance gains from photon recycling in metal halide perovskite solar cells remain uncertain due to high variability in material quality and the non-radiative recombination rate. In this work, we quantify the enhancement due to photon recycling for state-of-the-art perovskite Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3 (triple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 56 publications
6
60
0
Order By: Relevance
“…The experimental ELQE (8.4%) being larger than the numerical value Etint=7.8% shows that a high ILQE was achieved. For semiconductors with high ILQE, photon recycling, [ 42 ] i.e., the reabsorption of previously emitted photons within the perovskite, can increase the ELQE to values higher than what would be expected from the optical simulations, where photon recycling was neglected. [ 43 ] An experimental proof of internal photon recycling in perovskite solar cells was given by Pazos–Outón et al [ 44 ] Furthermore, Braly et al demonstrated perovskite films with 90% ILQE.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental ELQE (8.4%) being larger than the numerical value Etint=7.8% shows that a high ILQE was achieved. For semiconductors with high ILQE, photon recycling, [ 42 ] i.e., the reabsorption of previously emitted photons within the perovskite, can increase the ELQE to values higher than what would be expected from the optical simulations, where photon recycling was neglected. [ 43 ] An experimental proof of internal photon recycling in perovskite solar cells was given by Pazos–Outón et al [ 44 ] Furthermore, Braly et al demonstrated perovskite films with 90% ILQE.…”
Section: Resultsmentioning
confidence: 99%
“…The first is the radiative (or trivial) ET mechanism, i.e., PR, where emitted photons from one NC are reabsorbed by the neighboring NCs. PR has also been reported to enhance not only the transport properties in other types of perovskite systems [25][26][27][28][29][30][31] but also LED performances 32 .…”
Section: Imaging Of Exciton Diffusion In Pnc Filmsmentioning
confidence: 99%
“…In addition, also efforts to make single crystal perovskite solar cells are pursued [37,38] with a recent report of efficiencies exceeding 20% [38]. Close to the radiative limit, physical phenomena such as photon recycling [23,39,40] become important that are not or hardly relevant for most materials used in photovoltaics. Photon recycling specifies the process of photogeneration of electron-hole pairs by photons that are created by radiative recombination of electron-hole pairs.…”
Section: Introductionmentioning
confidence: 99%